‘‘Retour’’ et ‘‘reconquête’’ de la péninsule historique : discours et usages distinctifs autour du patrimoine de Fener et Çarşamba - Brian Chauvel (EchoGéo)
The transformation and preservation of Istanbul’s historic peninsula into protected historical heritage underpins a complex process of urban change. Contributing to the redefinition of the economic functions and the sometimes brutal renovation of the living space of the almost-island, the process engenders polemics that catch-up with the current political – even ideological – debates about fundamental societal questions. The discourses about this strongly symbolic space scrutinise directly what is (or should be) the social link; the city and its neighbourhoods are often seen as a metonymy of the entire Turkish society. With the help of observations conducted in two neighbourhoods – one (Fener) known for and visited because of its heritage rum, the other one (Çarşamba) cultivating an Islamic image – I explore the relations of distance and proximity and the symbolic borders that are both developing in these two districts.